Non-Western Concepts of Language: Are they of Any Use for the Scientific Knowledge of Language? - Bernárdez, Enrique (Complutense Journal of English Studies, 2017)
Few essential concepts have been so much debated as ‘language’; its definition opens the way to the development of new linguistic schools, approaches, etcetera. In this discussion, the Western views on language are taken for granted, as the only point of departure which guarantees and renders possible a scientifically sound science of language. The non-Western conceptualisations of language are very seldom mentioned in mainstream linguistic discussions and when they are, it is mainly as examples of non-scientific, naïve thinking – with a few well-known exceptions. This paper is organised in three parts: (1) Why -and how- the ‘non-Western’ conceptualisations of language are set aside as non-scientific, whereas the Western views and conceptualisations are seen as the central factor in linguistic theorising. (2) Examples of important ways of conceptualising language in three ancient literate cultures, viz. India, China, and Japan. (3) Conclusions on the main features of the ‘Eastern’ approaches which coincide with or may be profitable for present-day linguistics at large.